Development and validation of a clinically applicable score to classify cachexia stages in advanced cancer patients. Issue 2 (25th January 2018) - Zhou, Ting; Wang, Bangyan; Liu, Huiquan; Yang, Kaixiang; Thapa, Sudip; Zhang, Haowen; Li, Lu; Yu, Shiying
Abstract: Background: Cachexia is a multifactorial syndrome that is highly prevalent in advanced cancer patients and leads to progressive functional impairments. The classification of cachexia stages is essential for diagnosing and treating cachexia. However, there is a lack of simple tools with good discrimination for classifying cachexia stages. Therefore, our study aimed to develop a clinically applicable cachexia staging score (CSS) and validate its discrimination of clinical outcomes for different cachexia stages. Methods: Advanced cancer patients were enrolled in our study. A CSS comprising the following five components was developed: weight loss, a simple questionnaire of sarcopenia (SARC‐F), Eastern Cooperative Oncology Group, appetite loss, and abnormal biochemistry. According to the CSS, patients were classified into non‐cachexia, pre‐cachexia, cachexia, and refractory cachexia stages, and clinical outcomes were compared among the four groups. Results: Of the 297 participating patients, data from 259 patients were ultimately included. Based on the CSS, patients were classified into non‐cachexia ( n = 69), pre‐cachexia ( n = 68), cachexia ( n = 103), and refractory cachexia ( n = 19) stages. Patients with more severe cachexia stages had lower skeletal muscle indexes ( P = 0.002 and P = 0.004 in male and female patients, respectively), higher prevalence of sarcopenia ( P = 0.017 and P = 0.027 in male and female patients, respectively), more severe symptom burden ( P < 0.001), poorer quality of life ( P < 0.001 for all subscales except social well‐being), and shorter survival times ( P < 0.001). Conclusions: The CSS is a simple and clinically applicable tool with excellent discrimination for classifying cachexia stages. This score is extremely useful for the clinical treatment and prognosis of cachexia and for designing clinical trials.